Non‐invasive liver fibrosis score calculated by combination of virtual touch tissue quantification and serum liver functional tests in chronic hepatitis C patients. Issue 3 (20th June 2013) - Takaki, Shintaro; Kawakami, Yoshiiku; Miyaki, Daisuke; Nakahara, Takashi; Naeshiro, Noriaki; Murakami, Eisuke; Tanaka, Mio; Honda, Yohji; Yokoyama, Satoe; Nagaoki, Yuko; Kawaoka, Tomokazu; Hiramatsu, Akira; et al.
<x xml:space="preserve">Abstract</x> Aim Acoustic radiation force impulse (ARFI) technology, involving the shear wave velocity (SWV) with virtual touch tissue quantification (VTTQ), are currently available for the assessment of liver fibrosis, while there is no index derived from the combination of SWV and blood tests. The aim of this study was to develop a new index for assessment of liver fibrosis. Methods The subjects were 176 consecutive patients with hepatitis C (training set [n = 120] and validation set [n = 56]) who underwent liver biopsy in our institution. Results In the training set, SWV, international normalized ratio (INR) and alanine aminotransferase (ALT) correlated independently and significantly with fibrosis. According to this, we developed the VIA index = −1.282 + 0.965 × SWV + 1.785 INR + 0.00185 ALT. The areas under the receiver–operator curve (AUROC) of the VIA index were 0.838 for the diagnosis of significant fibrosis (≥F2), 0.904 for the severe fibrosis (≥F3) and 0.958 for the cirrhosis (F4) in the training set. While in the validation set, AUROC of the VIA index were 0.917 for F2 or higher, 0.906 for F3 or higher and 1.000 for F4, respectively. AUROC of the VIA index was improved compared to SWV alone, equivalent for VIA for the diagnosis of F2 or higher, and superior to that of FIB‐4 index and aspartate aminotransferase‐to‐platelet ratio index for the diagnosis of F3 or higher and F4. Conclusion The VIA index is potentially more useful for assessment of liver fibrosis than SWV alone, and easily and accurately measures liver fibrosis stage.